2006
DOI: 10.1007/s10865-006-9081-4
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Ethnic Discrimination in Relation to Daily Moods and Negative Social Interactions

Abstract: Ethnic discrimination experienced in an interpersonal context has been identified as a stressor contributing to racial disparities in health. Exposure to racism may influence the way people view their ongoing experiences, making it more likely that individuals will appraise new situations as threatening and harmful, adding to their overall stress burden. A multiethnic sample of 113 adults completed a diary page every 30 min for one day. The diary inquired about moods and perceptions of social interactions. Whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
128
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(139 citation statements)
references
References 61 publications
10
128
1
Order By: Relevance
“…Despite this relationship, unfairness was still associated with the MS independent of hostility. This result parallels work by Broudy et al [12] who observed that, when controlling for personality, discrimination was still associated with perceptions of social interactions as harassing. Harassment may trigger elevated physiological arousal in high hostile individuals [13], and unfair treatment certainly qualifies as harassment.…”
Section: Unfairness/discrimination and Health: Mechanisms Of Actionsupporting
confidence: 88%
“…Despite this relationship, unfairness was still associated with the MS independent of hostility. This result parallels work by Broudy et al [12] who observed that, when controlling for personality, discrimination was still associated with perceptions of social interactions as harassing. Harassment may trigger elevated physiological arousal in high hostile individuals [13], and unfair treatment certainly qualifies as harassment.…”
Section: Unfairness/discrimination and Health: Mechanisms Of Actionsupporting
confidence: 88%
“…75 In contrast, there is substantial, clear and consistent evidence that individual-level racism is associated with indices of psychological distress (e.g., negative affect, anger, depression, and anxiety), as well as personality characteristics (e.g., hostility, trait negative mood) that increase the experience of distress. 15,17,76,77 Racism may also influence cardiovascular responses to stress exposure. BP reactivity to stress has been identified as an independent predictor of the development of HTN.…”
Section: Racism and Htn: Examining The Associations Of Interpersonalmentioning
confidence: 99%
“…15 The discriminated individual may evaluate social interactions as harassment. 21 Vigilance also mediates the effects of discrimination on psychological distress. 20 Finally, discrimination may increase highrisk behaviors; for example, overt discrimination may result in social isolation and unhealthy behaviors.…”
Section: Introductionmentioning
confidence: 99%